Convenience of Efficiency Measures applied to Envelop of Laboratory Facility located in Burabai, Kazakhstan - Khamedov, Ruslan; Krymov, Dulat; Rojas-Solórzano, Luis R (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
A large portion of primary energy consumption in the world is associated to building sector; i.e. residential sector. Most studies agree on blaming space heating-cooling as the main reason of such high consumption, especially enhanced by excessive heat losses through windows and walls. Despite it is well known that proper selection of wall insulation and windows may minimize this issue, an economic assessment is needed to demonstrate the viability on a case-by-case basis. Therefore, the aim of this paper is to assess the techno-economic viability of using higher thermal-resistance insulation and windows instead of ordinary planned ones for an environmental laboratory, which will located in the region of Borovoe, Kazakhstan.
Keywords: Burabai; Laboratory Facility